Functional dyspepsia: A critical appraisal of the European consensus from a global perspective. Issue 9 (1st August 2021) - Moshiree, Baha; Talley, Nicholas J.
Abstract: The European Society for Neurogastroenterology and Motility's (ESNM) consensus document on functional dyspepsia (FD) has provided a critical review of the evidence for 36 statements highly relevant to the diagnosis and treatment of FD. We provide here our expert opinion on the North American, Australian and Asian assessments of the same topics discussed, and provide evidence where the ESNM consensus may deviate from those in the other continents. New and exciting data about the pathogenesis of FD are emerging including the possible central role of duodenal micro‐inflammation (most notably eosinophilic duodenitis and intestinal mast cell disease), but this is a very dynamic field with several gaps remaining in our understanding that are summarized in this review. Identification of non‐invasive biomarkers and testing of targeted therapies, including assessing the benefits of multidisciplinary teams in the management of FD, should be future priorities. Abstract : Graphical summary of current recommendations for functional dyspepsia as per the ESNM consensus of 2021.